Economic burden of Huntington's disease in Peru - Gustavo Silva-Paredes; Rosa M. Urbanos-Garrido; Miguel Inca-Martinez; Danielle Rabinowitz; Mario R. Cornejo-Olivas (BMC, 2019)
Abstract Background Huntington's disease (HD) is a devastating and fatal neurodegenerative disorder that leads to progressive disability, and over time to total dependence. The economic impact of HD on patients living in developing countries like Peru is still unknown. This study aims to estimate the economic burden by estimating direct and indirect costs of Huntington's disease in Peru, as well as the proportion of direct costs borne by patients and their families. Methods Disease-cost cross-sectional study where 97 participants and their primary caregivers were interviewed using a common questionnaire. Prevalence and human capital approaches were used to estimate direct and indirect costs, respectively. Results The average annual cost of HD reached USD 8120 per patient in 2015. Direct non-healthcare costs represented 78.3% of total cost, indirect costs 14.4% and direct healthcare costs the remaining 7.3%. The mean cost of HD increased with the degree of patient dependency: from USD 6572 for Barthel 4 & 5 (slight dependency and total independency, respectively) to USD 23,251 for Barthel 1 (total dependency). Direct costs were primarily financed by patients and their families. Conclusions The estimated annual cost of HD for Peruvian society reached USD 1.2 million in 2015. The cost impact of HD on patients and their families is very high, becoming catastrophic for most dependent patients, and thus making it essential to prioritize full coverage by the State.